Aplikasi Absensi Perkuliahan Menggunakan QR Code Dinamis Dan Metode Geofence Berbasis Android - Sinaga, Imperia Prestise; Susilo, Edi (Computer Science and Information Technology, 2024)
Attendance at lectures for students majoring in Electrical Engineering at Riau University is an important requirement for taking the Final Semester Examination (UAS). At the Department of Electrical Engineering, University of Riau, attendance activities use attendance sheets which are filled in by students and lecturers. Lecture attendance using this method is considered ineffective considering that students often forget to fill in lecture attendance when lectures are held boldly. Apart from that, this absence can still be easily manipulated by students, this is because some lecturers only fill in the material on the attendance sheet at the end of the lecture, after which the attendance sheet is given to the students, which causes absences to be left behind. In addition, the department head cannot directly observe whether the lectures are courageous or engaging. This research was conducted based on existing problems in the Department of Electrical Engineering with the aim of solving existing problems. The results of this research are a system created in the form of a website for lecturers to display a QR Code, and for department heads and study program coordinators to monitor ongoing lectures and an Android application for students to be able to take attendance. Implementation of the website system using the Laravel framework and the Kotlin programming language for Android applications. Testing is carried out on Android applications using four testing aspects, namely functionality, compatibility, portability and usability. The results obtained from this test were that the functionality test was successful, because there were no failures when running the system. And the compatibility test was successful, because the application was able to run together with other applications, and the portability test showed that the application could run using any version of Android. And the results of the usability test using UEQ show excellent results.